The Effectiveness of SBY Defense Strategy to Encounter China Power in International Security Threats 2009-2014 - Ulul Albab (UNIDA GONTOR, 2018)
AbstractThis study aims at explaining the effectiveness of President Susilo Bambang Yudhoyono's defense strategy in 2009-2014 to encounter international security threats especially in the rise of China. The defense strategy built by SBY is caused by the dynamism of international security which continues to grow. The condition can threaten the sovereignty of every country and disturb the stability of international security. This research is written down based on two concepts offered; those are national interest and balance of power. This study implements qualitative method that uses literature study of several books and journals. The technique of analyzing the data used in this research is inductive techniques. Study of literacy, journals, and some books are used in data collection to collect data for SBY defense effectiveness. The finding of this research shows that the strategy used by SBY to encounter international security threats are: (1) applying active free politic in foreign policy to establish defense cooperation; (2) designing MEF to meet the standard budget in building Indonesian military strength; (3) employing free from one block when any countries deal with conflict; and (4) maintaining peace and defending the sovereignty of citizens from external threats in accordance with Islam. It is not necessary to prioritize the group interests to determine the policy of defense strategy if the strategy designed by SBY has already given an impact on its effectiveness to safeguard the sovereignty of Indonesia. The author uses an inductive approach to analyze data. By collecting data or descripting relevant as well as from reliable sources with the ultimate goal of generalizing. The generalization is intended as a statement about relationship between two or more concepts; this statement can vary from simple to very complex Keywords: Strategy of defense; military; international security; sovereignty.